2020
DOI: 10.3389/fcell.2020.00646
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of the Anti-inflammatory Effects of Thymoquinone in Osteoarthritis and in silico Analysis of Inter-Related Pathways in Age-Related Degenerative Diseases

Abstract: Chronic inflammation is a common underlying factor in osteoarthritis (OA) and most age-related degenerative diseases. As conventional therapies help only in partial alleviation of symptoms in OA, stem cell-based therapies and herbal supplements are being widely explored. Thymoquinone (TQ), an active ingredient of Nigella sativa is reported to have immunomodulatory, anti-inflammatory and antioxidant properties. We evaluated the effects of TQ on bone marrow MSCs (BM-MSCs) derived from OA patients and its interre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…We have previously shown that natural products such as albiziasaponin-A, iso-orientin, and salvadorin can ameliorate the pathologies associated with AD in vivo ( Rasool et al, 2018 ) and that the natural products could be useful for the treatment of age-related degenerative diseases ( Kalamegam et al, 2020 ). In addition, we have recently shown that NGKD platforms can be successfully used to find drugs and natural products that may reverse disease-specific gene signatures ( Pushparaj et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that natural products such as albiziasaponin-A, iso-orientin, and salvadorin can ameliorate the pathologies associated with AD in vivo ( Rasool et al, 2018 ) and that the natural products could be useful for the treatment of age-related degenerative diseases ( Kalamegam et al, 2020 ). In addition, we have recently shown that NGKD platforms can be successfully used to find drugs and natural products that may reverse disease-specific gene signatures ( Pushparaj et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that thymoquinone has immunomodulatory and anti-inflammatory effects, that prevent the biosynthesis of important mediators in inflammatory processes and reduce proinflammatory cytokines such as interleukins (ILs) and TNF α. Besides, thymoquinone showed the immunomodulatory role in cellular and humoral immunity (19) (20) . Analysis of data obtained from the current study revealed that concanavalin A administration by retro-orbital route result in a remarkable elevation in both AST and ALT serum activities in comparison to the negative control group which received normal saline through retroorbital rout.…”
Section: Discussionmentioning
confidence: 99%
“…In reverse screening, the combined score helps to calculate the probability of targeting a given protein. Dual-based reverse screening has demonstrated high performance in predicting macromolecular targets (Kalamegam et al, 2020).…”
Section: Swisstargetpredictionmentioning
confidence: 99%